Penentuan Nilai Eigen Tak Dominan Matriks Hermit Menggunakan Metode Pangkat Invers Dengan Nilai Shift - Fitri Ariyani; Rizka Dini Humairoh (UIN Sultan Syarif Kasim Riau, 2015)
Inverse power method, can only be used to determine the eigenvalues of the matrix whose eigenvalues are real numbers. To determine the eigenvalues with complex matrices can be determined by using the value shift from implementing Gerschgorin theorem. Theorem Gerchgorin used in algebra to find the range of the complex eigenvalues of matrix berordo nx n. This shift value is the value of the approach was the dominant eigenvalues. This method is called inverse power method with shift value. Selection of a value shift greatly affect the number of iterations performed. In the process of determining the dominant eigenvalues do not need the initial vector. No dominant eigenvalues being used is not the dominant eigenvalues smallest of the eigenvalues no other dominant. This study discusses the eigenvalues not dominant on the berordo Hermit matrix 3 × 3, 4 × 4 and 5 × 5. Results obtained from the discussion is that no dominant eigenvalues of the third matrix is not too far from the election of his shift value.Keywords: Hermit matrix, not the dominant eigenvalues, the inverse power method with a shift value,